Cancer treatment-related financial toxicity in Japan: a scoping review - Itani, Yuki; Obama, Kyoko; Fujimori, Maiko; Saito, Junko; Uchitomi, Yosuke (Frontiers in Psychology, 2023)
Financial toxicity during cancer survival has been studied mainly in the United States; 47-49% of cancer survivors reported financial hardships and 12-63% reported debt owing to treatment costs. Financial toxicity is influenced by each country's economic status and healthcare system.We aimed to review the evidence on financial toxicity in Japan. A systematic search was performed using PubMed and Ichushi databases. We included English or Japanese peer-reviewed articles that (1) explored the experiences of cancer patients facing financial toxicity due to cancer diagnosis and treatment, (2) were specific to Japan, and (3) focused on the experiences of financial toxicities among cancer patients. Data were extracted focusing on the experiences of patients, families, and healthcare providers. The main themes were synthesized based on a previous study.The search yielded 632 citations from PubMed and 21 from Ichushi, and non-duplicates were identified. Of these, 31 articles were selected for full-text review. Literature was divided into studies describing the following elements: (a) risk factors for financial toxicity, (b) description of financial toxicity, (c) psychological reactions, (d) coping strategies for financial toxicity, and (e) impact on treatment outcomes. Only three studies reported comprehensive financial toxicity scores. Furthermore, treatment costs influenced physicians' treatment decisions, and patients and their families adopted various strategies to cope with treatment costs. Two studies showed that low current income and younger age were high-risk factors. As for utilization of the support system, approximately 70% of the patients used the high-cost medical expense system, 20% used the sickness benefit system, and 40% used the medical expense deduction system. Many cancer patients in Japan suffer from financial toxicity during cancer survival. One reason for this is that the awareness of the system supporting financial toxicity is insufficient and actual utilization is low. It is necessary to actively encourage patients to ask healthcare providers questions, improve the link between patients and the support system, reconstruct the support system design, and improve the method of publicizing the system.